HUMANISTIC COMMUNICATION APPROACH IN THE BROADCAST OF DA'WAH HIKMAH PAGI ON RADIO REPUBLIK INDONESIA (RRI) BANDAR LAMPUNG - Rosalina, Emilia; Purnama, Fadhli (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
A humanistic approach is an approach that pays attention to humanity. Do not think of it as an object that records a set of knowledge. Humanistics emphasizes the importance of preserving human existence, in the sense of helping human beings to be more humane, more cultured, as whole human beings. Based on the problems raised, researchers want to know more about the Humanistic Communication Approach of the Da'wah broadcast "Hikmah Pagi" broadcast by RRI Programa 1 Frequency 90.9Mhz Bandar Lampung. Hasi research of the author after conducting field research (field reserch) namely that da'i - da'i contained in Radio Republik Indonesia Bandar Lampung is da'i - da'i that has been chosen by the ministry of religion and also da'i - da'i which can unite the nation, not divide between religious people, ethnicity, race, ethnicity and culture of the Indonesian nation. The conclusion of this study is a Da'i who provides tausiah through audio media (radio) with interactive telephone with mas'u so as not to take sides with a people, race, ethnicity, tribe and culture. But da'i are more mammoth in shaping human beings to be more humane, more cultured, as whole and thriving human beings